ORIENTASI POLITIK DAN PERILAKU MEMILIH PENYANDANG DISABILITAS DI KOTA PEKANBARU PADA PEMILIHAN PRESIDEN TAHUN 2019 - Patra, Zulfiki; ", Hasanuddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
In the 2019 presidential and vice presidential elections, the participation of voters with disabilities in Pekanbaru City was very low. So it is very interesting to know the conditions of political orientation and voting behavior for people with disabilities in the 2019 presidential and vice presidential elections. This study aims to determine the political orientation and voting behavior of persons with disabilities in the 2019 presidential election.This study uses three approaches to political orientation, namely cognitive orientation, affective orientation and evaluative orientation. Choosing behavior also has three kinds of approaches, namely the sociological approach, the psychological approach and the rational choice approach. This research is structured based on qualitative research methods with data collection techniques in the form of interviews and documentation with informants who have been determined by the researcher.The results of this study indicate that the political orientation of persons with disabilities has three approaches. First, the cognitive orientation of persons with disabilities in general elections is good. Second, affective orientation, namely that elections are very important. Voters tend to say that the performance of the election administration at that time was ineffective, which resulted in voters being unable to exercise their voting rights. Third, the evaluative orientation, namely voters assessing the implementation of the 2019 presidential election did not run smoothly, there were still many frauds. Voters also think that a candidate deserves to be chosen because of their good track record and achievements that have been achieved by the candidate. Furthermore, the behavior of choosing persons with disabilities has three approaches. First, the sociological approach of persons with disabilities is influenced by organizations of persons with disabilities, the candidate's performance and religion. Second, the psychological approach of persons with disabilities is influenced by party identification, the issue of foreign workers, and candidate figures who have charismatic characteristics and the candidate's personality. Third, the rational approach of persons with disabilities is influenced by the vision and mission and programs, rationality sensitivity, one's wealth, achievements and debt issues. The tendency of choosing behavior is more influenced by disability organizations. Meanwhile, voters who do not use their voting rights generally do not receive ballots.Keywords: Political Orientation, Voting Behavior, Persons with Disabilities